Anatomoradiological topography of the mediastinum. Clasificación: Round Table Tumors of the mediastinum; introduction and coordination Luis M Falconi - González Maseda, Manuel; Mendoza, Daoiz (Cirugía del Uruguay, 1974)
Mediastinal tumors despite low often constitute a topic of interest practical in that they pose diagnostic problems clinical and difficulties in the approach route, express a varied moral pathology, with injuries of very diverse evolution and prognosis.